2010
DOI: 10.1002/app.32792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave irradiation on the physical properties and structures of wool fabric

Abstract: Microwaves are high frequency radio waves which are capable of penetrating many materials and causing heat to be generated in the process. To investigate the effect of microwave irradiation on the physical property, chemical structure, surface morphological structure, and fine structure of wool fabric, wool fabric was treated with microwave irradiation under variety of conditions in terms of the power and the time of microwave treatment. The breaking strength, breaking elongation, and whiteness of the treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Xue and Xin reported in their study of microwave irradiated wool fabric, that microwave heating is more efficient than conventional heating. 22 Annapurna et al reported that microwave irradiation could affect the macromolecular parameters, crystallographic structures and morphology of sisal fibre. 23 Mahmoodi et al found potential production of new environment-friendly textile fibres in their study of silk degumming using microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Xue and Xin reported in their study of microwave irradiated wool fabric, that microwave heating is more efficient than conventional heating. 22 Annapurna et al reported that microwave irradiation could affect the macromolecular parameters, crystallographic structures and morphology of sisal fibre. 23 Mahmoodi et al found potential production of new environment-friendly textile fibres in their study of silk degumming using microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave involves transfer of energy from electromagnetic waves into the treated material in the form of heat. Owing to the fact that exposure of polymeric materials to microwave for higher time interval possesses the danger of thermal induced degradation, hence, 120 s treatment might have resulted in degradation of strength providing cellulose moiety and rupturing of intermolecular polymer chains in the matrix which led to reduction in the mechanical properties of the composite films [91,99]. Based upon the comparative data analysis of F1 and F2 formulations treated with microwave for 60 s and 120 s, where F2 formulation proved significantly well and optimized in all physicochemical tests performed, therefore, it was decided to take only F2 formulation from this stage onward for further physicochemical analysis tests like ATR-FTIR, DSC, and SEM (discussed in later sections).…”
Section: Moisture Adsorptionmentioning
confidence: 99%
“…Wool has a relatively higher dielectric constant so that the use of high efficient microwave heating method in wool dyeing and finishing achieving energy saving and high efficiency has been the subject of considerable interest .The main disadvantage of a wide application of microwave energy in textile finishing is the negative influence of electromagnetic irradiation on the environment [37]. The separate of the Peanut red skin can be considered as a natural dye of worthy quickness properties together with super antibacterial for woolen fabrics [38].…”
Section: Microwave Irradiationmentioning
confidence: 99%